Sept Artistes Japonais de Paris a Noroit Arras. (Arras : Noroit Arras, 1993)
Imaï, Toshimitsu ; Inoué, Bukichi ; Kudo, Tetsumi ; Matsutani, Takesada ; Naraha, Takashi ; Satoru, Sato ; Tabuchi, Yasse
Sept Artistes Japonais de Paris a Noroit Arras, Noroit Arras, Arras, du 2 octobre au 19 décembre 1993
boek
Keywords: Japan